DATABASE AVIFAUNA PADA TIGA KAMPUS UNIVERSITAS LAMBUNG MANGKURAT DI BANJARBARU, INDONESIA - Tomi Utomo; Mochamad Arief Soendjoto; Suyanto Suyanto (Jurnal Sylva Scienteae, 2021)
Avifauna data of Lambung Mangkurat University (LMU), Banjarbaru are not yet available. This study aimed to obtain database regarding avifauna (bird) found or inhabited at LMU. Diurnal birds were observed on 3 campuses in the LMU Banjarbaru environment through transects and circles with a radius of 20 m between 07.00-10.00 and 15.30-18.30 with 3 repetitions. The database is packaged in the form of an 8-column table whose columns contain the serial number, family, species, and Indonesian names of the bird, the campus where the bird was found, the type of food observed being eaten, guilds, bird groupings, and bird status according to protection and its conservation. Twenty-three species or 14 bird families were observed. All species were found at the LMU Banjarbaru Campus. Fewer species were found on the other two campuses, namely the JPOK Campus and the PGSD Campus. The number of bird species observed is higher at the Main Campus of LMU, Banjarbaru because of its wider area. The plant species that live on the campus, especially woody plants, are more variedBelum tersedia data avifauna di lingkungan Universitas Lambung Mangkurat, Banjarbaru. Penelitian ini bertujuan untuk mendapatkan database avifauna yang ditemukan atau berhabitat di ULM. Burung diurnal diamati pada 3 kampus di lingkungan ULM Banjarbaru melalui transek dan lingkaran beradius 20 m antara jam 07.00-10.00 dan 15.30-18.30 dengan 3 kali ulangan. Database dikemas dalam bentuk tabel 8 kolom yang kolom-kolomnya memuat nomor urut, nama famili, nama spesies, dan nama Indonesia burung, kampus tempat burung tersebut ditemukan, jenis makanan yang teramati sedang dimakan, guild, kekelompokan burung, serta status burung menurut kelindunganan dan kekonservasiannya. Dua puluh tiga spesies atau 14 famili burung teramati. Semua spesies ditemukan pada Kampus Utama ULM Banjarbaru. Jumlah spesies lebih sedikit ditemukan di dua kampus lainnya, yaitu Kampus JPOK dan Kampus PGSD. Jumlah spesies burung teramati lebih banyak di Kampus Utama ULM, Banjarbaru karena areanya lebih luas. Spesies tumbuhan yang hidup di kampus itu pun, terutama tumbuhan berkayu lebih bervariasi